2007
DOI: 10.1111/j.1399-6576.2007.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after discharge from the intensive care unit during the early weekend period: a population‐based cohort study in Denmark

Abstract: Medical patients discharged from the ICU early in the weekends seem to have an increased mortality and risk of readmission to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Four studies have found increased mortality for patients who were admitted on weekends, compared to patients admitted on weekdays. [23][24][25][26][27][28] We also found an increased mortality risk associated with being admitted outside of normal working hours (Exhibit 1). Increased risk associated with off-hours admission has been demonstrated in studies of highly selected groups of patients with specific diagnoses such as myocardial infarction 26 and in studies of patients undergoing specific interventions, such as treatment of hip fracture 28 or cardiac arrest.…”
Section: Discussionmentioning
confidence: 65%
“…Four studies have found increased mortality for patients who were admitted on weekends, compared to patients admitted on weekdays. [23][24][25][26][27][28] We also found an increased mortality risk associated with being admitted outside of normal working hours (Exhibit 1). Increased risk associated with off-hours admission has been demonstrated in studies of highly selected groups of patients with specific diagnoses such as myocardial infarction 26 and in studies of patients undergoing specific interventions, such as treatment of hip fracture 28 or cardiac arrest.…”
Section: Discussionmentioning
confidence: 65%
“…Research has demonstrated that being discharged from ICU after hours increases the risk of readmission and post-ICU mortality (Gopal et al, 2010;Pilcher et al, 2007). Key reasons for this may include lower staffing levels on the wards at night time combined with inadequate clinical handover or poor appraisal of patient needs (Obel et al, 2007;Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Discharge season was included to control for seasonal illness variation (2527) and was categorized as September–November, December–February, March–May, and June–August. Two binary discharge time variables were included to explore the relevance of evening (14, 28, 29) and weekend transfers (30). As a proxy for severity of illness at admission, a predicted probability of mortality was estimated using Paediatric Index of Mortality (PIM) 2 (31).…”
Section: Methodsmentioning
confidence: 99%